Stevie [videorecording (DVD)] - James, Steve, 1955-; Hickam, Brenda; Fielding, Stephen Dale; Hagler, Verna; Hagler, Bernice; Hickam, Doug (Studio Home Entertainment : Distributed by Lions Gate Home Entertainment, 2003)
Returns to rural southern Illinois to reconnect with Stevie, a troubled young boy from ten years ago. The film began as a way of discovering what forces shaped Stevie's life. Part way through the filming, Stevie is arrested for a serious crime, and tears his family apart. The modest profile turned into a chronicle of Stevie, his broken family, the justice system and the filmmaker himself.